2006
DOI: 10.1309/dceq-d30v-5uej-a5gn
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Model of Antigen Retrieval Using a Peptide Array

Abstract: Even though antigen retrieval is highly denaturing, it paradoxically restores immunoreactivity after formalin fixation. It is unclear how this happens. We address this question using a peptide array to model formalin fixation and antigen retrieval. The peptides are linear stretches based on the native protein sequence, containing antibody epitopes of HER-2, estrogen receptor, progesterone receptor, and Ki-67. Of the 7 peptides, 6 retain their immunoreactivity after formalin fixation. However, if formalin fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…We examined the kinetics of formalin fixation and antigen retrieval in our peptide array model (Sompuram et al 2006a,b). We were particularly interested to determine whether the kinetics of antigen retrieval resembles the time course often associated with tissue sections.…”
Section: Similarity Of Reaction Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…We examined the kinetics of formalin fixation and antigen retrieval in our peptide array model (Sompuram et al 2006a,b). We were particularly interested to determine whether the kinetics of antigen retrieval resembles the time course often associated with tissue sections.…”
Section: Similarity Of Reaction Kineticsmentioning
confidence: 99%
“…The grid lines were superimposed after scanning the image to enhance clarity. Reproduced from Sompuram et al (2006).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are the first to demonstrate that heating could remove the masking of epitopes hidden due to the molecular configuration of native molecule (Kakimoto et al 2004). Sompuram et al (2004Sompuram et al ( , 2006 have reported on employing a model system with short peptide antigens covalently bound to glass slides to address the mechanism of formalin fixation and AR. Some short peptides including Ki-67 are sensitive to formalin and antigenicity is recovered by heating.…”
Section: Effects Of Heating Ar In Ihc and The Dot-blot Analyses With mentioning
confidence: 99%
“…Unlike cells and tissues, peptides can be printed on glass slides in a high throughput and reproducible fashion. The peptides can also be fixed in formalin, similar to formalin fixation of tissues, and behave immunochemically like the native antigen in tissue 15, 16. By comparing the staining of formalin-fixed peptides to unfixed peptides, IHC staining errors associated with antigen retrieval can be distinguished from errors in other analytic steps of the assay 12.…”
Section: Introductionmentioning
confidence: 99%